ANALISIS PENGARUH FAKTOR-FAKTOR MONETER DAN FISKAL TERHADAP JUMLAH UANG BEREDAR DI INDONESIA - Tri Risandewi (Pusbindiklat - LIPI, 2009)
The aims of this analysis are to see the effect of monetary factors such as foreign reserve and money multipliers and fiscal factor such as government expenditure toward money supply in Indonesia. The methods used in this analysis is Vector Autoregressive (VAR) or Vector Error Correction Model (VECM). This analysis uses a secondary data (three-month data) from 1986 until 2003. The result of this analysis, using VECM estimation, is that money supply, foreign reserve, and money multiplier have a short term and long term relationship. According to short term relationship, money supply and money multiplier have a positive correlation, with ceteris paribus assumption. Whereas a long term relationship shows that only foreign reserve and money multiplier have had a positive correlation, with ceteris paribus assumption.